Pengaruh Kenyamanan dan Lokasi Terhadap Loyalitas Pelanggan melalui Keputusan Pembelian Sebagai Variabel Intervening - Anisa Putri Rahmani (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
It is critical for Collective Co-working Space, which is a services company whose business operations include selling and providing services to consumers, to build a loyal customer base. The purpose of this study was to look into and figure out how convenience and location affect customer loyalty by using purchasing decisions as an intervening variable in a Collective Co-working Space in Yogyakarta's Special Region. This is a quantitative study that employs the questionnaire method as a data collection tool. The participants are all visitors or customers who come to Palagan Daerah Instimewa Yogyakarta's Collective Co-working Space. Software Statistical Product and Service Solutions (SPSS) and Software SmartPLS 3.0 will be used to manage data in this study. As a result, at the Yogyakarta Co-working Space Collective, convenience and location has a favorable and significant impact on customer loyalty. At the Yogyakarta Co-working Space Collective, purchasing decisions have a minor negative impact on client loyalty. At the Yogyakarta Co-working Space Collective, convenience and location has a favorable and significant impact on purchase decisions.